Fiscal Decentralization, Rural Industrialization, and Undocumented Labor Mobility in Rural China (1982-87) - Yiu Por (Vincent) Chen (Institute for the Study of Labor (IZA), 2015)
This paper explores the relationship between fiscal decentralization, which gave greater rural industrialization and fiscal authority to local governments, and the emergence of rural-rural undocumented inter-provincial labor migration during China's initial reform period. A Heckman model is employed to correct for the zero observation problems and to consistently estimate the labor mobility with a modified gravity equation. Given the institutional barriers, the fiscal decentralization has two contending effects on labor market integration: Local economic development promotes labor mobility, but local public goods crowding restrains the inflow of labor at the destination. The crowding effect is stronger at lower levels of government.
Keywords: H30; J61; J68; D72; 330; fiscal decentralization; local economic development; local public goods; rural labor mobility